Health Education and Public Health Collaboration in Building Healthier Communities: A Systematic Review - Alzahrani, Bandar Saleh Ahmed; Alghamdi, Ahmed Ali; Alasmari, Mohammed Ali Jaber; Saleem Alshehri, Abdulrahman Abdullah; Allah Alzubaidi, Asma Hamed Atiah; Ali Mutaen, Oqbah Hassan (Journal of Neonatal Surgery, 2025)
Background: KSA is in the process of an extensive reform of its health system. The national policy direction cited in Saudi Vision 2030 specifically emphasizes the need to move toward disease prevention, health promotion, and community-based care; therefore, strong and durable multi-sector collaboration also remains a strong pillar of better performance and sustainability of the system. Strategic engagement with academic institutions is needed to foster capacity development and research, and CSOs are focused on improving health literacy and empowering individuals and communities. Even with the strong policy mandate, structural integration across the care sectors (state, market, and community) remains weak. Objective: The main goal of this systematic review is to bring together the available empirical evidence on the context, mechanisms, effectiveness of, and barriers to the implementation of collaborative health education and public health interventions in the Kingdom of Saudi Arabia. Methodology: This systematic review protocol was developed in deliberation with the criteria articulated in PRISMA 2020 statement. The search strategy used the PICO framework and was conducted across key scholarly and health databases, and a targeted search of local academic journals, as well as grey literature (government reports, policy documents, and dissertations) relevant to KSA health. Conclusion: Health education programs that engage with CSOs and incorporate novel digital modalities are having a significant impact on generating awareness and an increase in knowledge regarding chronic disease primary prevention strategies among people in Saudi Arabia. It is extrapolated that policy options should be concentrated on creating mandates for structural integration, efficient regulation of PPPs, and accessible outreach to disadvantaged communities in a culturally appropriate manner..